Upaya Pemulihan Pariwisata Islam di Masa Pandemi (Studi pada Masjid Agung Demak) - Faridhatun Nikmah (UIN Raden Mas Said Surakarta, 2022)
The pandemi period resulted in a decrease in the number of tourists and pilgrims visiting the Great Mosque of Demak. The administrators of the Great Mosque of Demak are trying to conceptualize religious tourism services during the pandemi by implementing strict health protocols to reduce the spread of the Covid-19 virus. This research aims to find out the form of religious tourism services of the Great Mosque of Demak during the pandemi and to find out the concept of implementing religious tourism of the Great Mosque of Demak as an effort to recover during the pandemi. This research is a field research conducted at the Great Mosque of Demak because of the symptoms and events that occur in community groups. The method used in this research is to use descriptive qualitative research methods by describing the data in depth which is then reflected with the theory relevant to the research. The results of this study show that the services applied by religious tourism of the Great Mosque of Demak pay more attention to the 4K factor (cleanliness, health, security, and sustainability), while the concept in the development of religious tourism of the Great Mosque of Demak included the fulfillment of halal and friendly service facilities to the pilgrimage in the form of accommodation, restaurants, halal food, places of worship and adequate bathrooms, health clinics, libraries, museums, and other halal facilities. Thus, the concept and services carried out were used as an effort to restore Islamic tourism during the pandemi.